PENGARUH RASIO-RASIO EARLY WARNING SYSTEM (EWS) TERHADAP HARGA SAHAM PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Irfan Anggun Widiyono; Dian Safitri Pantja K; Siti Muntahanah (Majalah Imiah Manajemen & Bisnis, 2020)
This study aims to examine the significant effect of the claim expense ratio, the agent's balance to surplus ratio, and the premium growth ratio on the stock price of insurance companies listed on the Indonesia Stock Exchange in 2012-2015. This type of research is an empirical study with multiple regression analysis techniques. Based on the results of the regression analysis, it was obtained that the tcount value of the claim expense ratio variable (-1.289) was greater than the -ttable value (-1.683), the tcount value of the agent's balance to surplus ratio variable (-2.685) was smaller than the -ttable value (-1.683) while the tcount of premium growth ratio variable (1.912) is greater than ttable value (1.683). Thus, the first hypothesis is rejected, while the second and third hypotheses are accepted. Based on the results of data analysis, it can be concluded that the claim expense ratio has a negative but insignificant effect on the share price of insurance companies listed on the Indonesia Stock Exchange in 2012-2015. The agent's balance to surplus ratio has a significant negative effect on the insurance company's stock price, and the premium growth ratio also has a significant positive effect on stock prices. Therefore, there is an implication that as an effort to continue to increase its share price, company management needs to prioritize policies regarding the agent's balance to surplus ratio and premium growth. Companies can perform periodic and consistent evaluation actions relating to direct premium receivables, own capital and net premiums, use their own capital proportionately and control operating costs more efficiently in order to increase the company's premium income and net profit.